2002
DOI: 10.1016/s0034-4257(01)00241-3
|View full text |Cite
|
Sign up to set email alerts
|

Retrieval of vegetation clumping index using hot spot signatures measured by POLDER instrument

Abstract: The potential use of the information from a sampling of the bidirectional reflectance distribution function (BRDF) has suffered from the lack of solid applications in ecology, where it is expected to play the role of an advanced descriptor of vegetation as a complement to hyperspectral measurements. Such a shortcoming stems from the lack of consistent angular data sets with an adequate resolution at global scale. In this context, the POLDER instrument is particularly relevant because it acquires directional ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
49
0
1

Year Published

2003
2003
2017
2017

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 117 publications
(51 citation statements)
references
References 40 publications
(39 reference statements)
1
49
0
1
Order By: Relevance
“…Analogously, the HDS index ((ρ HS − ρ DS )/ρ DS ), which was proposed by Lacaze et al [29], has been widely used in recent research.…”
Section: Ndhd Ndvi and Hdvimentioning
confidence: 99%
See 2 more Smart Citations
“…Analogously, the HDS index ((ρ HS − ρ DS )/ρ DS ), which was proposed by Lacaze et al [29], has been widely used in recent research.…”
Section: Ndhd Ndvi and Hdvimentioning
confidence: 99%
“…2016, 8, 6 7 of 15 ρ )/ρ ), which was proposed by Lacaze et al [29], has been widely used in recent research. For HDS, the problem of mixed pixels becomes prominent at Proba-V's 300 m resolution: Some pixels containing mixed cropland and bare land demonstrate low ρ values, resulting in abnormal HDS values.…”
Section: Simulated Reflectance In Red and Nir Bandmentioning
confidence: 99%
See 1 more Smart Citation
“…Compared with LAI inversion from remote sensing, the clumping index retrieval from remote sensing data is less studied. Previous studies mainly focus on clumping index retrieving using Hotspot and Darkspot near-infrared (NIR) reflectance acquired by the multi-angular POLDER sensor [14,18]. However, the spatial resolution (6 km) of clumping index retrieved from POLDER data is too low to meet the demands of generating global 1 km or 500 m LAI products using MODIS data.…”
mentioning
confidence: 99%
“…Here, we assumed that the value of was 0.5, following Lacaze et al (2002), who showed that was about 0.5 for Canadian boreal coniferous forests.…”
Section: Modifications Made To Account For the Canopy-intercepted Snomentioning
confidence: 99%